2023
DOI: 10.1111/ahe.12965
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on the arterial vasculature of the brain in water buffalo (Bubalus bubalis): Clinical correlates

Masuood Ahmad John,
Rakshan Rashid,
Abrar A. Malik
et al.

Abstract: The present study was designed to provide a comprehensive analysis of the anatomical aspects of arterial blood vasculature in the water buffalo brains. Fifty cranial cavities of adult water buffaloes were opened via both the dorsal and ventral approaches and the arteries were exposed and photographed. The buffalo rostral epidural rete mirabile generally resembled that of large ruminants. The oculomotor, abducent and trigeminal nerves were intimately associated with the rostral rete. Similar to the majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Kiełtyka-Kurc et al ( 4 ) reported similar results in Bactrian camels. According to John et al ( 27 ), in buffalo, the RCA was observed to split into two to three branches at the anterodorsal aspect of the medial surface of the frontal lobe. Our study revealed that the rostral cerebral artery sends several cortical branches to the medial surface of the frontal and parietal lobes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiełtyka-Kurc et al ( 4 ) reported similar results in Bactrian camels. According to John et al ( 27 ), in buffalo, the RCA was observed to split into two to three branches at the anterodorsal aspect of the medial surface of the frontal lobe. Our study revealed that the rostral cerebral artery sends several cortical branches to the medial surface of the frontal and parietal lobes.…”
Section: Discussionmentioning
confidence: 99%
“…The caudal branch supplied the posterior and inferior aspects of the occipital lobe. While the rostral branches supplied the caudomedial area of the occipital lobe ( 27 ). The same observation has been made in humans, showing that several cortical branches originate from the posterior cerebral artery, including the anterior temporal, posterior temporal, medial occipital, and lateral occipital arteries ( 57 ).…”
Section: Discussionmentioning
confidence: 99%